No influence of noradrenaline manipulation on acute exercise-induced increase of brain-derived neurotrophic factor - Goekint, Maaike; Heyman, Elsa; Roelands, Bart; Njemini, Rose; Bautmans, Ivan; Mets, Tony; Meeusen, Romain (Medicine and science in sports and exercise, 2008)
To examine the influence of a selective noradrenaline reuptake inhibitor (SNRI) on the exercise-induced increase in circulating brain-derived neurotrophic factor (BDNF). In a double-blind, placebo-controlled, crossover design, 11 young, healthy male subjects were treated with either placebo or reboxetine. On each occasion, they performed a 60-min cycling exercise at 55% of their maximal power output (Wmax) followed by a time trial (TT) at 75% of Wmax. HR and ratings of perceived exertion were measured. Blood samples were taken at four time points. An increase in serum BDNF was found after exercise without any influence of drug administration on BDNF levels. Serum BDNF returned to resting levels after 15 min of recovery. Time trial (TT) performance was significantly worse after reboxetine intake. Serum cortisol increased in both trials during and after exercise and was significantly higher in the reboxetine trial. Also, HR was increased with reboxetine intake, probably because of the sympathomimetic effect of SNRI. Midterm memory was significantly impaired after the exercise protocol without difference between reboxetine and placebo trial. The administration of an SNRI has no effect on the exercise-induced increase in BDNF. However, effects were seen on serum cortisol, HR, and memory. Future research should focus on the effect of regular exercise training in combination with several reuptake inhibitors in both healthy and depressed subjects on BDNF and memory.